Answer:
The solution to the system of equations is
x = -2
y = 5
Step-by-step explanation:
Given the pair of equations:
3x + y = -1 ............................................................................(1)
2x - 2y = -14 .......................................................................(2)
To solve the system by elimination, first of all
Divide equation (2) by 2, to simply have:
x - y = -7 ...............................................................................(3)
To eliminate y
Add equation (1) and (3) together
3x + x + y - y = -1 - 7
4x = -8
Divide both sides by 4
x = -8/4 = -2
To eliminate x
Multiply equation (3) by 3
3x - 3y = -21 .........................................................................(4)
Subtract equation (4) from equation (1)
3x - 3x + y - (-3y) = -1 - (-21)
y + 3y = -1 + 21
4y = 20
Divide both sides by 4
y = 20/4 = 5
Therefore, x = -2, and y = 5